Juridical Analysis of Law Enforcement Against Perpetrators of Criminal Acts Human Smuggling (Research Study of the General Criminal Investigation Directorate of the National Police) - Mesniar Novrina Sari Duha; Ramon Nofrial; Darwis Anatami; Erniyanti; Soerya Respationo (MultiTech Publisher, 2023)
One of the cross-border crimes that often utilize Indonesian territory as a transit point is human smuggling, popularly known as people smuggling. Human smuggling is classified as a transnational organized crime with a wide area of operation. Indonesia is one of the areas of the country targeted by illegal immigrants before being smuggled to their destination, namely countries on the Australian continent. This phenomenon has made human smuggling a criminal offense taken very seriously by all levels of the world community. In less than two decades, significant changes in Indonesia's strategic environment in the form of upheaval in the Asian region have encouraged human smuggling crimes and become one of the most exciting types of transnational crimes. Riau Islands, as one of the provinces in Indonesia, is a strategic area that has sea borders with Singapore and Malaysia, causing Riau Islands to become a stopover place for illegal migrants and the perpetrators so that there are many human smuggling mafias roaming around looking for victims. One of the factors triggering human smuggling that is difficult to eradicate and still occurs today in the Riau Islands is the existence of sectoral egos and various forms of modus operandi carried out by human smugglers.